Anchoring Supramolecular Polymers to Human Red Blood Cells by Combining Dynamic Covalent and Non‐Covalent Chemistries. (18th August 2020) - Morgese, Giulia; de Waal, Bas F. M.; Varela‐Aramburu, Silvia; Palmans, Anja R. A.; Albertazzi, Lorenzo; Meijer, E. W.
Abstract: Understanding cell/material interactions is essential to design functional cell‐responsive materials. While the scientific literature abounds with formulations of biomimetic materials, only a fraction of them focused on mechanisms of the molecular interactions between cells and material. To provide new knowledge on the strategies for materials/cell recognition and binding, supramolecular benzene‐1, 3, 5‐tricarboxamide copolymers bearing benzoxaborole moieties are anchored on the surface of human erythrocytes via benzoxaborole/sialic‐acid binding. This interaction based on both dynamic covalent and non‐covalent chemistries is visualized in real time by means of total internal reflection fluorescence microscopy. Exploiting this imaging method, we observe that the functional copolymers specifically interact with the cell surface. An optimal fiber affinity towards the cells as a function of benzoxaborole concentration demonstrates the crucial role of multivalency in these cell/material interactions. Abstract : Drawn to the blood : When benzene‐1, 3, 5‐tricarboxamide 1D‐fibers are decorated with benzoxaborole moieties, a dynamic interaction with human red blood cells is induced via the adaptive covalent reaction between boronic acids and cell sialic acids. Total internal reflection fluorescence microscopy is exploited as a powerful tool to allow real‐time imaging of cells/fiber binding, revealing the multivalency of this interaction.